THE CHARACTER AND MORAL VALUES IN THE MOVIE ‘WONDER’ BY STEPHEN CHBOSKY - Nanik Ristiah Sari Halim; Oom Rohmah Syamsudin (Universitas Indraprasta PGRI, 2020)
This research aims to analyze the characters and moral values in the “Wonder” movie by Stephen Chbosky. The method used in this research is descriptive-qualitative which aims to describe the character and moral values in the Wonder” movie. Data obtained, analyzed, and explained based on dialogue data contained in the movie protagonist, antagonist, secondary, extras, round dan flat, and based on moral values: commitment to something greater than oneself, self-respect but with humility, self-discipline, and acceptance of personal responsibility, respect and caring for others, caring for other living things an environment. This shows the moral Value that dominates and wants to be conveyed is the Value of caring for others.